2021
DOI: 10.1186/s12909-021-02752-2
|View full text |Cite
|
Sign up to set email alerts
|

A guide for evaluation of online learning in medical education: a qualitative reflective analysis

Abstract: Background With the strike of Covid-19, an unprecedented rapid shift to remote learning happened worldwide with a paradigm shift to online learning from an institutional adjuvant luxury package and learner choice into a forced solo choice. This raises the question of quality assurance. While some groups have already established standards for online courses, teaching and programs yet very little information is included on methodology of their development and very little emphasis is placed on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 36 publications
1
20
0
1
Order By: Relevance
“…However, these students believe, that some form of blended learning is likely to remain after the pandemic is controlled. In Libya, less than 30% of medical students responding to a study survey had participated in formal medical education coursework via e-learning prior to the pandemic [ 15 ]. Most of that same study group (64.7%) disagreed that e-learning can be implemented in Libya.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these students believe, that some form of blended learning is likely to remain after the pandemic is controlled. In Libya, less than 30% of medical students responding to a study survey had participated in formal medical education coursework via e-learning prior to the pandemic [ 15 ]. Most of that same study group (64.7%) disagreed that e-learning can be implemented in Libya.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, most suggested that online method could be more interactive. In another study [ 15 ], students suggested that regular formative assessment could accomplish more student engagement. Other students in the same study suggested using games, quizzes, and multimedia for the online classes to be more interesting.…”
Section: Discussionmentioning
confidence: 99%
“…This precipitous and near universal adoption of remote learning modalities also necessitates a framework for their evaluation, both for quality assurance as well as for the development of standards and best practice indicators as they have been identified in the areas of organizational capacity, educational effectiveness, and human resources. 29 We were especially interested in examining how online instructional methods affected student involvement in and understanding of the learning material as well as their perception of course quality. To measure these effects, we examined students' performance on the course learning assessments and their subsequent evaluation of course content and delivery.…”
Section: Discussionmentioning
confidence: 99%
“…Agreed standards are also increasingly needed to enhance online learning experiences given the current challenges, including successfully transferring courses and assessments online [ 61 , 69 , 70 , 71 ]. Alongside this, as mentioned, there must be good availability and access to the Internet and appropriate software packages, as well as availability of computers among students, especially those from disadvantaged backgrounds, to facilitate e-learning [ 50 , 61 , 62 , 71 , 72 , 73 ].…”
Section: Introductionmentioning
confidence: 99%